2001
DOI: 10.1037/1076-8971.7.2.267
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clinical and scientific expert testimony on juror decision making in capital sentencing.

Abstract: Future dangerousness of a criminal defendant is an important consideration in eight states' capital sentencing provisions, and in Oregon and Texas a finding of dangerousness is an essential requirement for the imposition of the death penalty (Worrell, 1987).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 69 publications
5
123
1
1
Order By: Relevance
“…Numerous concerns exist over the use of mock juror research despite its application to various law-related topics including, but not limited to, comprehensibility of jury instructions (e.g., Rose & Ogloff, 2001) and expert witness testimony (e.g., Krauss & Sales, 2001 in that jury-eligible and student samples resulted in nearly identical verdict outcomes. Also germane to the present study is that previous mock juror research showed student and jury samples as equally persuaded by expert witnesses (Hinkle, Smeltzer, Allen, & King, 1983).…”
Section: Justifying Use Of Mock Jurorsmentioning
confidence: 99%
“…Numerous concerns exist over the use of mock juror research despite its application to various law-related topics including, but not limited to, comprehensibility of jury instructions (e.g., Rose & Ogloff, 2001) and expert witness testimony (e.g., Krauss & Sales, 2001 in that jury-eligible and student samples resulted in nearly identical verdict outcomes. Also germane to the present study is that previous mock juror research showed student and jury samples as equally persuaded by expert witnesses (Hinkle, Smeltzer, Allen, & King, 1983).…”
Section: Justifying Use Of Mock Jurorsmentioning
confidence: 99%
“…Although past research (Krauss & Lee, 2003;Krauss & Sales, 2001) has compared the influence of expert testimony based on actuarial instruments to pure clinical judgments, we know of no research to date that has also examined a guided professional judgment risk assessment tool and its influence on juror decision-making. Given the increased use of such instruments, this is an oversight in need of correction.…”
Section: Advances In Risk Assessmentmentioning
confidence: 99%
“…Kansas v. Hendricks, 1997;Kansas v. Crane, 2002). Critics within the legal and psychological fields have questioned the ethics (Faust & Ziskin, 1988;Lavin & Sales, 1998), the validity (Cunningham & Reidy, 1999, 2002Edens, Petrila, & Buffington-Vollum, 2001), and the biasing effects that these potentially unreliable expert predictions might have on jury decisions (Guy & Edens, 2003;Krauss & Lee, 2003;Krauss & Sales, 2001). Although considerable advances have been made in the area of dangerousness prediction or risk assessment validity (see, e.g., Quinsey, Harris, Rice, & Cormier, 1998;Webster, Douglas, Eaves, & Hart, 1997), there still remains considerable doubt whether these new procedures are being used in actual practice (see, e.g., Melton, Petrila, Poythress, & Slobogin, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations